The prevalence of undernutrition and associated risk factors in people with tuberculosis in Lao People’s Democratic Republic - Donekham Inthavong; Hend Elsayed; Phonesavanh Keonakhone; Vilath Seevisay; Somdeth Souksanh; Sakhone Suthepmany; Misouk Chanthavong; Xaysomvang Keodavong; Phonesavanh Kommanivanh; Phitsada Siphanthong; Phengsy Sengmany; Buahome Sisounon; et al. (PLoS ONE, 2025)
Objective Undernutrition is common in individuals with tuberculosis (TB). There is a bidirectional association between having TB and undernutrition; undernutrition increases the risk of having active TB, and having TB worsen undernutrition by reducing appetite and food intake. Despite World Health Organization (WHO) recommendations for comprehensive nutritional assessment and counselling for people with TB, systematic implementation is lacking in Lao People’s Democratic Republic (Lao PDR), leading to an insufficient understanding of undernutrition prevalence in this population. Methods A facility-based cross-sectional survey was conducted between March 2022 and March 2023 in six central and provincial hospitals in Lao PDR. We assessed the prevalence of undernutrition in 312 people diagnosed with TB at TB diagnosis using body mass index (BMI). Undernutrition was defined as a BMI < 18.5 kg/m2, and severe undernutrition as a BMI below 16.5 kg/m2. Data on demographic, clinical and economic information and nutritional status were extracted from an intervention study assessing the effect of nutritional counselling and feeding on the financial burden of TB and TB treatment outcomes. Results Of 312 participants, 40.7% (n = 127) were with undernutrition (BMI < 18.5 kg/m2) at the time of TB diagnosis. 20.5% (n = 64) with severe undernutrition (BMI < 16.5 kg/m2). Factors significantly associated with undernutrition included age group 15–24 years (Adjusted odds ratio (AOR) 6.9, 95% confidence interval [95%CI]: 2.2–23.2), drug-resistant TB (AOR 3.2, 95%CI: 1.0–11.8), experiences of hospitalization until TB diagnosis (AOR 3.4, 95%CI: 2.0–5.9), self-reported weight loss (AOR 7.8, 95%CI: 2.3–36.4), and below the poverty line at TB diagnosis (AOR 1.9, 95%CI: 1.0–3.6). Conclusion A high prevalence of undernutrition was observed in people diagnosed with TB at their diagnosis in Lao PDR. The findings underscore the urgent need for systematic nutritional assessment and counselling as integral components of TB care to identify and address undernutrition, thereby enhancing overall health outcomes for individuals with TB.